Cover Image:. Issue 4 (17th April 2022) - Unknown
Abstract : The circadian clock, an internal time‐keeping mechanism, drives many physiological processes during the 24‐h day. The core oscillators respond to the resetting of environmental timing cues. The rhythmic outputs include leaves and petals movement, sunflower heliotropism, stomatal opening and closing, oscillation of cytosolic free calcium, and the resistance responses to biotic and abiotic stresses, etc (Page 792–811).